Association between dental caries, periodontal status, and personality traits of 35-44-year-old adults in Bareilly City, Uttar Pradesh, India - Anushka Gupta; Nagesh Laxminarayan Shetty (Wolters Kluwer Medknow Publications, 2019)
Background: A majority of human diseases are said to have psychosomatic origin. Certain pathologic entities have already been accepted to have a psychological basis. Personality of an individual is one such psychological entity, but the research on relationship between personality traits and oral diseases is scarce. Aim: To find an association between the personality traits of the participants and their dental caries and periodontal status. Materials and Methods: A descriptive survey (questionnaire + clinical examination) using consecutive sampling technique was conducted. The study population consisted of 450 adults, aged 35-44 years. Sociodemographic details, oral hygiene practices, dental health seeking behavior, dietary practices, decayed-missing-filled teeth (DMFT) index, and community periodontal index were recorded. Eysenck Personality Questionnaire Revised-Short Form (Hindi version) was used to measure personality traits. The data were analyzed using SPSS version 19. Kruskal-Wallis ANOVA followed by Mann-Whitney U-test (post hoc), linear regression analysis using enter method, and logistic regression analysis were done. Results: As per the lie scale, 72 individuals were excluded, of which only 375 were further analyzed. There were 282 (62.7%) extroverts, 76 (16.9%) neurotics, 17 (3.8%) were a combination of extroversion and neuroticism, and 3 (0.7%) were a combination of extraversion and psychoticism. Dental caries (P = 0.002) and periodontal disease (P = 0.005) were significantly less in extroverts in comparison to other personality traits. Conclusions: Among different personality traits, extroverts were found to have lesser dental caries and better periodontal status. Thus, personality traits as one of the determinants of oral health may throw more light on the psychosomatic link of oral diseases, hence on the importance of behavior management.